The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1590/s0034-70942004000200002
|View full text |Cite
|
Sign up to set email alerts
|

Sufentanil subaracnóideo associado à bupivacaína hiperbárica para analgesia de parto: É possível reduzir a dose do opióide?

Abstract: The association of sufentanil to hyperbaric bupivacaine improves quality and prolongs analgesia duration. When associated to 2.5 mg hyperbaric bupivacaine, there is no benefit in administering more than 2.5 microg of sufentanil for labor pain relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
1
1
0
2
Order By: Relevance
“…The results demonstrated that CSE lasts longer when sufentanil is associated with the local anesthetic. This is corroborated by the studies of other authors, although the duration in our study was longer 19 . The group who underwent CSE only with local anesthetic also had greater prevalence of hypotension as soon as the block was performed, because the dose of local anesthetic in this group was greater than in the sufentanil group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results demonstrated that CSE lasts longer when sufentanil is associated with the local anesthetic. This is corroborated by the studies of other authors, although the duration in our study was longer 19 . The group who underwent CSE only with local anesthetic also had greater prevalence of hypotension as soon as the block was performed, because the dose of local anesthetic in this group was greater than in the sufentanil group.…”
Section: Discussionsupporting
confidence: 93%
“…Os resultados evidenciaram que a duração do BC quando se acrescenta sufentanil ao anestésico local é maior do que quando realizado somente com anestésico local. Esse fato é corroborado por resultados de outros autores, embora a duração neste estudo tenha sido superior 19 . O grupo submetido ao BC somente com anestésico local também teve prevalência maior de hipotensão arterial logo após a instalação do bloqueio, pois a dose de anestésico local utilizada neste grupo foi maior que no grupo do sufentanil.…”
Section: Discussionunclassified
“…Esses resultados estão de acordo com os descritos na literatura, nos quais o relato de prurido é maior após a administração de opióide pela via subaracnóidea 15 . A incidência, após injeção subaracnóidea de sufentanil, é elevada, variando de 25% a 90% [11][12][13][16][17][18] . Em estudo com parturientes submetidas à analgesia de parto com a técnica de duplo-bloqueio, nas quais foi administrado o sufentanil, nas doses de 5 µg ou 10 µg, foi observado que a redução na dose do opióide não alterou a freqüência ou a intensidade do prurido 13 .…”
Section: Discussionunclassified
“…These results are in agreement with those in the literature, in which the incidence of pruritus is greater after the administration of subarachnoid opioid 15 . The incidence after the subarachnoid administration of sufentanil varies from 25% to 90% [11][12][13][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Segundo Lee et al, (2011), a infusão intratecal de 20 μg de fentanil ou 2,5 μg de SUF associados a BVC hiperbárica a 0,5%, promove analgesia intraoperatória adequada, sem efeitos adversos significativos para a mãe e neonato. Esses resultados corroboram com os apresentados por Yamaguchi et al (2004), em que a adição de SUF intratecal nas doses de 2,5 μg e 5 μg associados a 2,5 mg de BVC hiperbárica, melhorou a qualidade e prolongou a duração da analgesia de parto. Outro estudo, comparando a BVC (0,125%) coadministrada com SUF (7,5 μg) por via epidural durante o trabalho de parto, indicou ocorrência de analgesia rápida e completa (Gautier, et al, 1999).…”
Section: Morfina Fentanil Sufentanilunclassified